The taxidermist's daughter - Mosse, Kate, 1961- (HarperCollins, 2016)
Joining her fellow English villagers in a misty churchyard on St. Mark's Eve, a taxidermist's daughter reflects on the mysterious downfall of her father's once-famous museum before discovering the body of a stranger whose death unlocks dark memories.